1997
DOI: 10.1074/jbc.272.17.11622
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast SRP54 Interacts with a Specific Subset of Thylakoid Precursor Proteins

Abstract: Signal recognition particles (SRPs) have been identified in organisms as diverse as mycoplasma and mammals; in several cases these SRPs have been shown to play a key role in protein targeting. In each case the recognition of appropriate targeting signals is mediated by SRP subunits related to the 54-kDa protein of mammalian SRP (SRP54). In this study we have characterized the specificity of 54CP, a chloroplast homologue of SRP54 which is located in the chloroplast stroma. We have used a nascent chain cross-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
53
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 61 publications
4
53
0
Order By: Relevance
“…They did not identify interactions between cpSecA and OEC33 or pCytf, although it is known that OEC33 requires cpSecA for thylakoid membrane translocation (39,40). The lack of interaction between cpSecA and Cytf in this study (38) is most likely due to the absence of thylakoid membranes in their experimental setup. The observed affinity of cpSRP54 for pCytf is most likely related to the heterologous nature of the ribosome (see Ref.…”
Section: Figmentioning
confidence: 43%
See 1 more Smart Citation
“…They did not identify interactions between cpSecA and OEC33 or pCytf, although it is known that OEC33 requires cpSecA for thylakoid membrane translocation (39,40). The lack of interaction between cpSecA and Cytf in this study (38) is most likely due to the absence of thylakoid membranes in their experimental setup. The observed affinity of cpSRP54 for pCytf is most likely related to the heterologous nature of the ribosome (see Ref.…”
Section: Figmentioning
confidence: 43%
“…High et al (38) identified interactions between cpSRP54 and different thylakoid proteins using a wheat germ translation system with 80 S ribosomes. In their study, truncated transcripts were translated and stable 80 S RNCs were purified and incubated with purified chloroplast stroma devoid of thylakoid membranes.…”
Section: Figmentioning
confidence: 99%
“…With the exception of a synthetic peptide (see below), all reagents, enzymes, and standards were purchased commercially. Previously described plasmids were used for in vitro transcription͞translation of pLHCP (psAB80XD͞4) (13), tOE23 (14), iOE33 (15), and TM3-PC (12). However, the TM3-PC translation product, which codes for a fusion protein between the carboxyl-terminal third of pLHCP and the mature domain of plastocyanin (PCm), is designated here as pLHCP to more clearly indicate the amino acids derived from pLHCP.…”
Section: Methodsmentioning
confidence: 99%
“…Comparison of cpSRP and eukaryotic SRP to cotranslationally bind RNCs revealed that the substrate requirement for SRP binding is similar (12); signal sequence overall hydrophobicity stimulates SRP binding to RNCs. In these assays, the signal peptide of an endoplasmic reticulum-targeted protein (e.g.…”
mentioning
confidence: 99%
“…These routes include the spontaneous insertion of proteins (18), and signal recognition particle-dependent (9), ⌬pH-dependent (6, 21), and SecA-dependent pathways (22,33). A twin-arginine motif is specifically recognized by components of the ⌬pH-dependent pathway, and hydrophobic sequences are favored by the signal recognition particle-dependent pathway (12,13). The specificity of cpSecA for the Sec-dependent chloroplast signals observed here provides a mechanism for avoiding precursor proteins with those features.…”
mentioning
confidence: 99%